Monitoring intracranial pressure in paediatric brain injury. Issue 10 (October 2022) - Patel, Shil; Shaw, Eloise; Davies, Patrick; Stewart, Craig
Abstract: Acute paediatric brain injury is a major cause of mortality and morbidity worldwide. Historically raised intracranial pressure (ICP) has been the hallmark for escalating management in acute brain injuries, however there is limited evidence behind this, and no UK approved guidance advocating its use. This article summarises the current role of ICP monitoring within traumatic and non-traumatic paediatric brain injury and discusses the evidence base for different modalities and their uses.